Influence of Liquidity Risk Hedging on Performance of Real Estate Firms in Meru County, Kenya - Mburugu, Kenneth Kamari; Mutea , Fredrick; Rintari , Nancy (International Journal of Professional Practice, 2023)
Real estate investments are long-term and capital intensive projects which outperform other asset classes attracting many investors. Real estate contributes greatly to the gross domestic product of many nations. However, financial risks, such as liquidity risk, may largely affect the performance of real estate firms. Though financial risks are global, Kenya experiences high uncertainty of returns due to market volatility and economic fluctuations. This study aimed to assess the influence of Liquidity risk hedging on the performance of real estate firms in Meru County, Kenya. The study adopted a descriptive survey design, and was anchored on the liquidity preference theory. Questionnaires and secondary data schedules were used to collect data from 24 real estate firms. Using stratified random sampling method, a sample size of 131 officers was derived using Krejcie and Morgan formula. The senior managers and financial, operations, risk, sales and legal officers from the 24 real estate firms constituted the respondents. To test the reliability and validity of the instruments, 14 questionnaires were pretested in 3 real estate firms in Tharaka Nithi County. Data was analyzed through SPSS version 23, and results presented using descriptive and inferential statistics. The results indicated that liquidity risk hedging had the highest positive influence on NOI, ROE, but less influence on ROA. The study recommends that banks and the financial market players train the real estate firms on available financial innovations so as to hedge risks. The findings challenge the existing paradigms and offers a new perspective on the use of derivatives in hedging real estate liquidity risk. This research aligns with the Kenyan government housing project agenda, and provides a platform for a further discussion on pitfalls to avoid in real estate investments, and the available opportunities